Gene action and heterosis studies for grain Fe and Zn content in rice (Oryza sativa L.) - Sandhyarani Das1, Devraj Lenka1, Digbijaya Swain1*, Swapan Kumar Tripathy1, Bandita Jena1, Manasi Dash³, Lakesh Muduli1, Abinash Mishra1 and T.B. Bagchi2 (Electronic Journal of Plant Breeding, 2024)
Development of rice genotypes possessing high yielding potential; with increased grain iron content is the need of the hour to tackle hidden hunger. Considering the above said fact, genetical analysis was conducted in six improved cultivars along with 15 potential crosses thereof. Analysis of variance for combining ability revealed significant differences in GCA and SCA variances for grain yield as well as for iron and zinc content, indicating the possibility of realization of development of iron fortified varieties with higher yielding potential. The preponderance of additive gene action for these two important characters i.e., iron and zinc content indicate that selection will be highly rewarding for genetic improvement pertaining to these two traits. The genotype Gouri was found to be very good combiner for both grain yield (0.93) and iron content of grain (2.04). Similarly, genotype Sebati was found as a very good combiner for both grain yield (0.13) and zinc content of grain (0.65). Some of the superior crosses identified concerning both grain yield and grain iron content were Birupa / Pradeep, Sebati / Gouri, Sebati / Pratap, Gouri / Pradeep and Pratap / Pradeep. Hence, these specific crosses can be used in further breeding programme for the improvement of both grain yield as well as grain iron content. The crosses viz., Bhanja / Pratap and Bhanja / Sebati were found to be superior crosses for both grain yield and grain zinc content.